Time Series Analysis of Commercial Yellowfin Tuna (Thunnus albacares) Production in South Cotabato, Philippines, Using the SARIMA Model - Karl Evan R. Pama (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
A stochastic time series analysis was done through the SARIMA model to identify the characteristics of production in terms of trend and seasonality, develop the optimal SARIMA model based on certain information criteria and diagnostics, evaluate the accuracy of in-sample and out-of-sample forecast, and create a forecast for the production. Quarterly production data of commercial yellowfin tuna (Thunnus albacares) in South Cotabato during the years 2002 to 2021 were subjected to Box-Jenkins modeling procedure such as logarithmic transformation of data, differencing, checking for stationarity, identifying the optimal model through information criteria, estimating model parameters, and performing model diagnostics. It was found that the commercial yellowfin tuna production was fluctuating significantly but showed cyclical trend and seasonal pattern; the production is usually lower in Q3 but higher in Q2 and Q4. As for the results obtained from diagnostic checking, it could be deduced that SARIMA(1,1,1)(1,1,1)[4] model was deemed as the best-fitting model since it provided the minimum AIC and AICc values. Based on this model, it could be predicted in the next few years from 2026 to 2030 that there would be no remarkable growth or decline in production, and only slight fluctuation will be expected because of the season. It is essential to highlight, however, that there is a limit to the use of the univariate approach in time series forecasting, as even though the model will give accurate results when the environment remains constant, it does not account for sudden changes in ecological and economic environments.